Carbapenemase-producing Enterobacteriaceae in a Portuguese hospital – a five-year retrospective study - Gorgulho, A (2020)
Background: Our hospital experienced an outbreak of OXA-48-producing Enterobacteriaceae, triggering this study. We aimed to describe the population with carbapenemase-producing Enterobacteriaceae (CPE) in our hospital from 2014 to 2018, the phenotypic and genotypic characteristics of isolates, and strategies to stop the outbreak. Methods: We performed a retrospective study, including every patient with CPE species in a clinical sample. Epidemiology, risk factors, treatment and outcomes were gathered from medical records. Results: A total 113 patients were included, ranging from 5 in 2015 to 83 in 2018. In 2018 the number of CPE went from 4 in May to 20 in July. With the implemented measures, propagation stopped. Implantable devices were present in 36% of patients and open wounds in 34%. Antibiotics had been prescribed to 71% of patients in the prior 30 days and most of the patients had been hospitalized for more than 5 days prior to sample collection or had a hospital stay in the previous year.Klebsiella pneumoniae was the most common species (87%). OXA-48 (62%) and Klebsiella pneumoniae-carbapenemase (KPC) (15%) were the most common carbapenemases, with OXA-48 being implicated in the 2018 outbreak. The case fatality rate at 30 days was 32%. Combination therapy resulted in less mortality. Conclusions: While KPC is the most common carbapenemase in Europe and Portugal, we experienced an important OXA-48 outbreak. Surveillance should be in place as these isolates are probably spreading. Effective communication, multidisciplinary team work and proper infection control measures are some of the best strategies during outbreaks.